HUBUNGAN KARAKTERISTIK PENDERITA DENGAN TINGKAT KEPATUHAN PENGGUNAAN OBAT ANTIHIPERTENSI PADA PENDERITA HIPERTENSI DI PUSKESMAS AMPLAS: THE RELATIONSHIP BETWEEN PATIENT CHARACTERISTICS AND THE LEVEL OF COMPLIANCE WITH THE USE OF ANTYHIPERTENSIVE DRUGS IN HYPERTENSIVE PATIENTS AT AMPLAS HEALTH CENTRE - Utami, Tiyas; Lubis, Ichwan Alamsyah; Siregar, Julahir Hodmatua; Novasyra, Aulia (Jurnal Kedokteran STM (Sains dan Teknologi Medik), 2026)
Hypertension is a major factor in global health problems. Treatment of hypertension requires long-term therapy so that patient compliance is a major factor determining the success of treatment. This study aims to analyze the relationship between respondent characteristics (age, gender, education level and therapy regimen) with the level of compliance with the use of antihypertensive drugs. Quantitative method was used with cross sectional approach and purposive sampling technique. The level of compliance with taking medication was measured by the Morisky Meducation Adherence Scale-8 questionnaire. The results of the analysis on 51 respondents showed a relationship between age and the level of compliance with taking antihypertensive drugs (p value 0.015), the relationship between education level and the level of compliance with taking antihypertensive drugs (p value 0.005). There is no relationship between gender and the level of adherence to taking antihypertensive drugs with a p value of 0.051 (p>0.05) and there is no relationship between therapy regimens with the level of adherence to taking antihypertensive drugs with a p value of 0.062 (p>0.05). There is a relationship between age and education level with the level of compliance with the use of antihypertensive drugs and there is no relationship between gender & therapy regimen with the level of compliance. AbstrakHipertensi merupakan faktor utama masalah kesehatan global. Pengobatan hipertensi membutuhkan terapi jangka panjang sehingga kepatuhan pasien merupakan faktor utama penentu keberhasilan pengobatan. Penelitian ini bertujuan menganalisis hubungan antara karakteristik responden (usia, jenis kelamin, tingkat pendidikan dan regimen terapi) dengan tingkat kepatuhan penggunaan obat antihipertensi. Digunakan metode kuantitatif dengan pendekatan cross sectional dan teknik purposive sampling. Tingkat kepatuhan minum obat diukur dengan kuesioner Morisky Meducation Adherence Scale-8. Hasil analisa pada 51 responden menunjukkan hubungan usia dengan tingkat kepatuhan minum obat antihipertensi (nilai p 0,015), hubungan tingkat pendidikan dengan tingkat kepatuhan minum obat antihipertensi (nilai p 0,005). Tidak terdapat hubungan jenis kelamin dengan tingkat kepatuhan minum obat antihipertensi dengan tingkat kepatuhan minum obat antihipertensi dengan nilai p 0,051 (p>0,05) dan tidak terdapat hubungan regimen terapi dengan tingkat kepatuhan minum obat antihipertensi dengan nilai p 0,062 (p>0,05). Terdapat hubungan usia dan tingkat pendidikan dengan tingkat kepatuhan penggunaan obat antihipertensi dan tidak terdapat hubungan jenis kelamin & regimen terapi dengan tingkat kepatuhan.